The Touristic Local Systems as a means to re-balance territorial differences in Sicily - Vittorio Ruggiero; Luigi Scrofani (European Regional Science Association (ERSA), 2005)
The Italian new law (n.135/2001) about the re-organization of touristic activities of Regions has contributed to re-think all the resources related to touristic valorisation in a systemic view point. In fact according to the new approach, the Local Touristic System (STL in Italian law) regards not only the naturalistic and the cultural resources and the hotels but also the economic and services activities that can related to tourism. Although Sicilian Region has not instituted its official STL, in our paper we will try to define the STL in Sicily in a particular point of view. In fact we will consider not only the touristic areas but also the areas less developed, because the systemic approach allows us to use the touristic activities as a factor of territorial re-balance instead of territorial polarization. We also will consider the principal touristic port related to the STL, according the point of view of an integration among ports and its surrounding areas. So the ports become a door to the inner areas full of naturalistic and cultural resources.
Keywords: 330